The “Hishtavut” Motif in S.Y. Agnon’s Novel, The Day Before Yesterday - Nagar, Irit (MiKAN, 2022)
The article explores the “Hishtavut” motif in S.Y Agnon’s novel Tmol Shilshom (The Day Before Yesterday, published in 1945). The term “Midat Hahishtavut,” meaning “state of tranquility,” is well-known in Jewish thought and describes an ideal plane a religious person aspires to attain. The term has undergone changes over the years in the writing of various thinkers, who each offer their own interpretation of how a person should behave to be faithful to the work of God. This article seeks to reveal the centrality of the term in S.Y. Agnon’s novel Tmol Shilshom and argues that through the widespread use of the “state of tranquility” the novel reflects Jewish society during the Second Aliyah, a time that involved both religious and social complexity.